Maternal depression and associated risk factors (Research, Society and Development, 2019)
This study aimed to analyze the frequency of postpartum depression and associated risk factors in a sample of mothers of infants born in a medium-sized city in the central region of Rio Grande do Sul (RS). The study was carried out in a School Hospital in which the infants underwent neonatal hearing screening, from March to May 2010. The study sample consisted of 183 infant-mother dyads. To collect data, an interview script was used on socioeconomic, demographic, obstetrical and psychosocial information and the Beck Depression Inventory (BDI). The majority of the sample studied did not present evidence of postpartum depression (56.1%), and the risk factors associated with depression were low family income and no pregnancy planning. The precarious socioeconomic conditions of women and the non-planning of gestation were the factors that significantly influenced the onset of depression in the postpartum period in the sample studied.